Penerapan Metode Menghafal Nadhom sebagai Upaya Melatih Daya Ingat Peserta Didik Kelas VI pada Mata Pelajaran Muatan Lokal Diniyah Sekolah Dasar Negeri Brangkal I Bandarkedungmulyo Jombang - Muhammad Najihul Huda; Fathur Rofi'i; Siti Faizah (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2026)
ABSTRACT This study aims to determine the application of the Nadhom memorization method as an effort to train the memory of sixth-grade students in the local content subject at Brangkal I Elementary School, Bandarkedungmulyo, Jombang. The study used a qualitative approach with a case study method, motivated by the phenomenon of religion-based learning that is difficult for students to memorize and digest. Data collection was carried out through observation, documentation, and interviews with the principal, supervising teachers, and students to obtain data, which was then analyzed in depth by the researcher. The data analysis used the Huberman and Mils model through three stages: data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the Nadhom memorization method involved several stages, including: preparation and consultation with the principal, preparing teaching modules and media, and implementing the lesson plan in class. Several obstacles encountered during the implementation of the Nadhom memorization method included: lack of student interest, basic problems reading Arabic Pegon, boredom, differences in student abilities, and the presence of students with special needs. Keywords: Memorization Method, Nadhom, Memory